PENGEMBANGAN MODEL PEMBERDAYAAN BAGI PENGOLAH IKAN GUNA MENINGKATKAN PENDAPATAN (Studi Kasus Pada Pengolah Ikan Di Kabupaten Cilacap) - Ida Ayu Kade Rachmawati K., Christiawan Hendratmoko, Budi Istiyanto, (Paradigma, 2015)
The aims of this research are to analyze the power of fish-processor, evaluated by economic and non economic aspect, to analyze the performance of fish-processing by R/C ratio, to analyze the role of stakeholders in increasing fish-processorâs income, and to formulate the strategy of empowerment for fish-processor.Primary data populated from 109 respondents in South Cilacap Subdistrict.Â The analysis methodsÂ used are descriptive statistics, crosstab analysis, and analytical of process hierarchy.The results of study indicate that the powers of fish-processor are still less, they have low level income with R/C ratio 1,03 up to 1,67.Â The roles of stakeholders toward coastal area communityÂ are still poor.Â Therefore, we need strategy to empower them by giving loan (credit), reviving the fish-processorâs organization, and giving information and training about modern technical of fish-processing.Â Keywords:Â the power of fish- processor;Â stakeholders;Â R/C ratio